2017
DOI: 10.4103/1319-2442.206439
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoporosis in patients with chronic kidney disease (stages 3–5) in comparison with age- and sex-matched controls: A study from Kashmir Valley Tertiary Care Center

Abstract: Chronic kidney disease (CKD) is associated with a range of metabolic bone diseases. Fracture rates are higher in CKD patients than age-matched controls throughout all the five stages of CKD. Dialysis patients have 4 times as many hip fractures as expected for their age. CKD forms an independent risk factor for osteoporosis, even in the absence of traditional risk factors. This study was carried out at the nephrology unit in a tertiary care center of Kashmir to know the prevalence of osteoporosis in CKD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…CKD has an increasing prevalence in the general population and is a frequent comorbidity in patients with hip fractures. 9 , 18 In our study, the prevalence of patients with eGFR <60 mL/min/1.73 m 2 was 6.0% (n=15), and our study showed that eGFR was an independent factor of preoperative DVT in patients with hip fractures. Patients with CKD had a higher increased risk of occurrence of preoperative DVT than those with normal kidney function, which was consistent with data from previous studies.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…CKD has an increasing prevalence in the general population and is a frequent comorbidity in patients with hip fractures. 9 , 18 In our study, the prevalence of patients with eGFR <60 mL/min/1.73 m 2 was 6.0% (n=15), and our study showed that eGFR was an independent factor of preoperative DVT in patients with hip fractures. Patients with CKD had a higher increased risk of occurrence of preoperative DVT than those with normal kidney function, which was consistent with data from previous studies.…”
Section: Discussionsupporting
confidence: 54%
“…Renal insufficiency is a common comorbid disease and is associated with a range of metabolic bone diseases; it is especially common among elderly patients with hip fractures. 9 Renal insufficiency typically results in the occurrence of chronic kidney disease (CKD), and patients with CKD usually experience increased rates of morbidity and mortality. 10 Autonomic dysfunction, myocyte dysfunction, altered electrolyte metabolism, and cardiac fibrosis may contribute to cardiovascular disease in patients with CKD, which is the leading cause of morbidity and mortality in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis or osteopenia is another common complication of CKD. The prevalence of osteoporosis in CKD patients ranged from 18% to 32%, while osteopenia was found in up to 57% of patients [ 58 , 59 ]. A significantly higher prevalence of osteoporosis and fractures has been reported in patients with end-stage renal disease (ESKD), especially in patients on hemodialysis compared to those on peritoneal dialysis [ 60 ].…”
Section: Iron Deficiency and Bone Lossmentioning
confidence: 99%
“…Therefore, early diagnosis and prevention are extremely important. Studies have shown that chronic kidney disease (CKD) is an independent risk factor for osteoporosis (Najar et al, 2017). Patients with renal insufficiency have a significantly lower bone mineral density (BMD) (Tseng et al, 2014;Bezerra de Carvalho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%